2002
DOI: 10.1152/ajpheart.00128.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pial arteriole dilation during somatosensory stimulation is not mediated by an increase in CSF metabolites

Abstract: Ngai, Al C., and H. Richard Winn. Pial arteriole dilation during somatosensory stimulation is not mediated by an increase in CSF metabolites. Am J Physiol Heart Circ Physiol 282: H902-H907, 2002; 10.1152/ajpheart.00128.2001.-Pial arterioles supplying the hindlimb somatosensory cortex dilate in response to contralateral sciatic nerve stimulation. The mechanism of this pial vasodilation is not well understood. One possibility is that vasoactive metabolites released during brain activation may diffuse to subarach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…In the macrovasculature, the time-of-flight ͑TOF͒ effect is sensitive to blood flow velocity change and may enhance stimuli-induced BOLD contrast. The TOF contrast was observed previously in pial arterial vessels 34,35 as well as in cerebral cortical veins ͑23% flow velocity increase͒. 36 A recent study demonstrated that the variation of the HR ͑e.g., time-to-peak and FWHM͒ depended on vessel diameters, orientations, and the flow velocity contained within a voxel.…”
Section: Discussionmentioning
confidence: 60%
“…In the macrovasculature, the time-of-flight ͑TOF͒ effect is sensitive to blood flow velocity change and may enhance stimuli-induced BOLD contrast. The TOF contrast was observed previously in pial arterial vessels 34,35 as well as in cerebral cortical veins ͑23% flow velocity increase͒. 36 A recent study demonstrated that the variation of the HR ͑e.g., time-to-peak and FWHM͒ depended on vessel diameters, orientations, and the flow velocity contained within a voxel.…”
Section: Discussionmentioning
confidence: 60%
“…Specific branches of pial arteries also dilate rapidly, extending up to >1 mm away from the center of the responding region (Li et al 2003, Ngai & Winn 2002) with recent evidence supporting high-speed retrograde propagation of vasodilation (Chen et al 2011, Iadecola et al 1997, Chen et al 2014). …”
Section: Spatiotemporal Properties Of the Hemodynamic Responsementioning
confidence: 88%
“…This would require that vasoactive transmitters diffuse tens to hundreds of microns to the pial vessels. Ngai and Winn (2002) directly tested the hypothesis that surface vessels respond to spillover of vasodilators by flushing the pial vessels with ACSF during sensory stimulation. They found that flushing the pial surface with ACSF had no effect on sensory evoked dilation of pial arterioles, but did reduce CO 2 evoked dilation, supporting the idea that CO 2 dilates vessels via a different pathway than neural activity.…”
Section: Discussionmentioning
confidence: 99%